ANALISIS PENGARUH EMPLOYEE ENGAGEMENT, KEPUASAN KERJA DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PADA INDOMARET - Triwahyono, Anang; Yani, Achmad (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
Indomaret is a minimarket network that provides basic needs and daily needs. In 1997 the company developed the first franchised outlet business in Indonesia, after having more than 230 stores. In 2015 there were 11,400 stores, 60% of which were self-owned and the rest were public property. Indomaret is spread evenly from Sumatra, Java, Madura, Bali, Lombok, Kalimantan and Sulawesi. The company motto is